Effect of Medicaid Expansion on Colorectal Cancer Screening Rates. Issue 1 (January 2019) - Zerhouni, Yasmin A.; Trinh, Quoc-Dien; Lipsitz, Stuart; Goldberg, Joel; Irani, Jennifer; Bleday, Ronald; Haider, Adil H.; Melnitchouk, Nelya
Abstract : BACKGROUND: Colorectal cancer screening decreases incidence and improves survival. Minorities and low-income patients have lower screening rates. The Affordable Care Act increased insurance coverage for low-income Americans by funding Medicaid expansion. Not all states expanded Medicaid. The effect of Medicaid expansion on colorectal cancer screening is unknown. OBJECTIVE: This study aimed to evaluate if Medicaid expansion improved colorectal cancer screening for minorities and low-income patients. DESIGN: We used the Behavior Risk Factor Surveillance System, a nationally representative health-related telephone survey, to compare colorectal cancer screening rates from 2012 to 2016 based on Medicaid expansion status. A difference-in-difference analysis was used to compare the trends. SETTINGS: All states were included in this survey. PATIENTS: Respondents aged 50 to 64 from the early expansion, 2014 expansion, and nonexpansion states were selected. INTERVENTIONS: Medicaid expansion was funded by the Affordable Care Act. MAIN OUTCOME MEASURES: The primary outcome measured was the screening rate based on US Preventive Services Task Force guidelines. RESULTS: Overall screening in expansion states increased (early, +4.5%, p < 0.001; 2014, +1.3%, p = 0.17) compared with nonexpansion states. Screening among low-income respondents increased in early expansion states (+5.7%; p = 0.003), whereas there was no change in 2014 expansion states compared with nonexpansion states (2014, –0.3%, p = 0.89). For blacks, there was a significant increase in early expansion states, but no change in 2014 expansion states (early, +8.1%, p = 0.045; 2014, –1.5%, p = 0.64). There was no significant change for Hispanic respondents in early or 2014 expansion states compared with nonexpansion states (early, +6.5%, p = 0.11; 2014, +1.2%, p = 0.77). LIMITATIONS: Survey data are subject to response and recall bias. Factors other than Medicaid expansion may have influenced the screening rate. CONCLUSIONS: The colorectal cancer screening rate has increased in all settings, but expansion accelerated the increases in early expansion states and among low-income and black respondents; however, there was no similar increase for Hispanic respondents. It will be important to continue to monitor the effects of Medicaid expansion on colorectal cancer care, especially the incidence by stage and mortality. SeeVideo Abstract athttp://links.lww.com/DCR/A792 .